2005
DOI: 10.1182/blood-2004-07-2618
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant subcellular targeting of the G185R neutrophil elastase mutant associated with severe congenital neutropenia induces premature apoptosis of differentiating promyelocytes

Abstract: Mutations in the ELA2 gene encoding neutrophil elastase (NE) are present in most patients with severe congenital neutropenia (SCN). However, the mechanisms by which these mutations cause neutropenia remain unknown. To investigate the effects of mutant NE expression on granulopoiesis, we used the HL-60 promyelocytic cell line retrovirally transduced with the G185R NE mutant that is associated with a severe SCN phenotype. We show that the mutant enzyme accelerates apoptosis of differentiating but not of prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 45 publications
4
57
1
Order By: Relevance
“…Effects on proteolytic activity, on cellular trafficking and on unfolded protein response (UPR) have been demonstrated only for subgroups of ELANE mutations, respectively. [11][12][13][14] Furthermore, other ELANE mutations described as causative for congenital neutropenia, e.g. p.Val72Met 1 were also categorized as benign by the prediction algorithms.…”
Section: Resultsmentioning
confidence: 99%
“…Effects on proteolytic activity, on cellular trafficking and on unfolded protein response (UPR) have been demonstrated only for subgroups of ELANE mutations, respectively. [11][12][13][14] Furthermore, other ELANE mutations described as causative for congenital neutropenia, e.g. p.Val72Met 1 were also categorized as benign by the prediction algorithms.…”
Section: Resultsmentioning
confidence: 99%
“…[54][55][56] There have been several contradicting reports on disturbances in the subcellular localization of neutrophil elastase caused by mutations associated with CN or SCN. 10,57 It has particularly been suggested that mutations in neutrophil elastase affect the sorting to granules via disorganization of putative transmembrane and cytosolic domains. 58 Our finding that lack of serglycin completely prevents granule localization of elastase argues against a significant role of putative transmembrane and cytosolic domains of neutrophil elastase in granule targeting.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to inappropriate ANC monitoring, G-CSF treatment related cycle modification, incomplete mutation spectrum data, phenotype diversification by modifier genes and additional somatic mutations, especially in the colony stimulating factor 3 receptor gene (CSF3R) [11][12][13][14]15 16,17]. The monomeric serine chymotryptic-type protease neutrophil elastase is a major component of neutrophil granulocyte azurophilic granules and is named after its first known substrate elastin [129].…”
Section: Elane Deficiencymentioning
confidence: 99%